Analysis of Baby Stunting Prevalence Causing Factors in the Pandemy Era COVID-19 - Ringoringo, Harapan Parlindungan; Sholihah, Qomariyatus; Maharany, Dike; Kuncoro, Wahyudi; Luthfansa, Imam; Lenggono, Kumoro Asto (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The research objectives are to analyze prevalence factors stunting of a baby during the COVID-19 pandemic. The prevalence rate of stunting under five in Indonesia is high due to the lack of awareness and knowledge of the community. This could prevent the government from fulfilling the need for quality human resources in the future. METHODS: This study is an analytical descriptive study that aims to explain the factors that cause the prevalence of stunting under five in the era of the COVID-19 pandemic. Data analysis using fishbone diagrams, hazard identification, and risk assessment of the six factors. RESULTS: Furthermore, the analysis was carried out using hazard identification and risk assessment and obtained several risk categories, namely low risk of 13.3%, moderate 40%, high by 20%, and extreme by 26.7%. CONCLUSION: The recommendations for improvement given refer to the extreme category because it is felt that this category has the highest urgency. The recommendations given are expected to assist the government in achieving the target of reducing the prevalence rate of stunting under five in Indonesia.